Analisis Faktor-Faktor yang Mempengaruhi Profitabilitas Pada Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia - Carina Ruslan; Vargo Christian L. Tobing (Komunitas Dosen Indonesia, 2022)
This study aims to determine the factors that affect profitability in the food and beverage sub-sector manufacturing sector listed on the Indonesia Stock Exchange for the period 2016-2020. The population consists of 26 companies with the sample technique used is purposive sampling. The sample in this study are companies that meet the criteria, there are 11 companies with 55 data. The results of the research on the t test are that the Current Ratio partially has a positive and significant effect on Return on Assets, Total Asset Turnover partially has no effect on Return on Assets and Debt to Equity Ratio partially has a positive and significant effect on return on assets. The results of the research on the f test are that Return on Assets is simultaneously influenced by the Current Ratio, Total Asset Turnover, and Debt to Equity Ratio. The results of the coefficient of determination prove that Return on Assets is explained by the Current Ratio, Total Asset Turnover, and Debt to Equity Ratio of 17.9% and the remaining 82.1% percentage is explained by other variables not included in this study